2016
DOI: 10.1037/hea0000355
|View full text |Cite
|
Sign up to set email alerts
|

Childhood socioeconomic status and cardiovascular reactivity and recovery among Black and White men: Mitigating effects of psychological resources.

Abstract: Objective To evaluate a possible physiological mechanism underlying links between low childhood socioeconomic status (SES) and poor adult health by a) testing whether childhood SES is prospectively related to cardiovascular responses to laboratory stress in adulthood, and b) by determining whether psychological resources buffer cardiovascular reactivity and promote better recovery from stress. Methods Participants (n= 246; 55% Black; mean age= 32 years) were from a population-based sample of men in Pittsburg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 82 publications
3
17
1
Order By: Relevance
“…These findings provide support for a link between SES and HRV but also suggest that this relationship may vary as a function of age, race, and assessment condition (i.e., stressful versus non-stressful). Whereas low SES has previously been linked to impaired HRV recovery following a stressful task among Europeans in the Whitehall II cohort [49], a recent study observed a negative association between adulthood SES and HRV following as stressor in 246 African American and European American men followed since 1988 as part of the Pittsburgh Youth Study [44]. This latter finding raises the possibility that the association between SES and both resting and stress-related HRV may be more nuanced and warrants further study.…”
Section: Socioeconomic Factorsmentioning
confidence: 92%
See 1 more Smart Citation
“…These findings provide support for a link between SES and HRV but also suggest that this relationship may vary as a function of age, race, and assessment condition (i.e., stressful versus non-stressful). Whereas low SES has previously been linked to impaired HRV recovery following a stressful task among Europeans in the Whitehall II cohort [49], a recent study observed a negative association between adulthood SES and HRV following as stressor in 246 African American and European American men followed since 1988 as part of the Pittsburgh Youth Study [44]. This latter finding raises the possibility that the association between SES and both resting and stress-related HRV may be more nuanced and warrants further study.…”
Section: Socioeconomic Factorsmentioning
confidence: 92%
“…Autonomic dysfunction has been characterized as one potential mechanism linking lower socioeconomic status (SES) to racial disparities in health [44][45][46][47]. There is growing evidence that low SES is associated with lower basal HRV [46], as well as impaired recovery in HRV following stressful tasks [45,48].…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…Among those who were eligible but did not participate, 22 declined participation, 19 failed to respond to messages or missed appointments, and 42 could not be located. Of the 312 men, some no longer lived in the Pittsburgh area, so 267 men participated in the laboratory protocol (36,37). Analyses were restricted to the 267 men with laboratory data.…”
Section: Participantsmentioning
confidence: 99%
“…A subsample participated during adolescence in a psychophysiology study (Fite et al, 2010;Gatzke-Kopp, Raine, Loeber, Stouthamer-Loeber, & Steinhauer, 2002;Loeber, Pardini, Stouthamer-Loeber, & Raine, 2007). A majority of the individuals from this substudy were also available for testing in a subsequent study that assessed cardiovascular health and medical history (Boylan, Jennings, & Matthews, 2016) that occurred when the individuals were in early middle age. This sample allowed us to examine the stability of the key HR and HR reactivity variables as a function of developmental period and how these related to risk for CVD.…”
mentioning
confidence: 99%